Quantification of energy transfer processes from crystalline silicon to erbium. Issue 6 (23rd January 2023) - Liu, Huan; Kentsch, Ulrich; Yue, Fangyu; Mesli, Abdelmadjid; Dan, Yaping
Abstract : Typical energy transfer from silicon to Erbium through Erbium-Related Defect States (ERDS) in Er: c-Si. Abstract : Erbium-implanted silicon is considered as a promising system to realize electrically pumped light sources at the communication band due to the stable luminescence of Er ions at 1536 nm. However, this system suffers from an extremely low luminescence efficiency at room temperature. Quantitatively, understanding the energy transfer processes in the system is critical to improving the Er luminescence efficiency, which unfortunately remains ambiguous. In this article, we managed to establish a complete methodology that can quantitatively describe the energy transfer processes from Si to Er. We first employed the Kohlrausch's function to analyze the transient photoluminescence (PL) of Er in silicon at different temperatures, from which we found the emission flux and effective decay rate of excited Er ions in steady state. These extracted parameters were used in the widely accepted energy transfer processes to analyze Er PL behaviors as a function of temperature (80–300 K) and excitation power. Interestingly, we managed to quantitatively find almost all important physical parameters of the energy transfer process including the energy transfer efficiency from Er-related defects to Er ions (21.6% at room temperature), the PhotoLuminescence Quantum Yield (PLQY, 0.45% at room temperature) and a record high optically active Er concentration (2 × 10 19 cm −3 ). In this system, high defect density, rather than severe energy back-transfer process, becomes the limiting factor for efficient Er emission. Further careful analysis indicates that the Er/O/B-doped silicon has a potential to reach a PLQY of 3.5% if the defects in the Si bandgap are properly passivated.